Economy and banking sector performance: Spillover effect of Uncertainty of Covid-19 on Non-performing loans of Turkish Agricultural sector - Olorogun, Lukman Ayinde; Kamil, Anton Abdulbasah (Data Science: Journal of Computing and Applied Informatics, 2025)
This spillover index research paper tries to find connectedness between Non-performing loans (NPL) and Covid-19 global pandemic specifically in the Turkish agricultural sector. The research covers variables of NPL, Geopolitical risk index (GPR), Fishing, Agriculture, Non-performing loans to total assets (NPL_TCL), Return on assets (ROA), Return on equity (ROE). The data for this research includes a monthly time series dataset covering between Dec. 2004–April 2020. To perform the statistical analysis descriptive statistics, correlation matrix with its T-statistics and probabilities, and Dielbold and Yilmaz index were adopted to uncover the level of connectedness among the group. The descriptive statistics results of the group reveal that all variables understudy were contributing factors to the increase of NPL of the banking sector in general. Specifically, the agricultural sector’s NPL has a significant effect on the banking sector’s aggregate NPLs. The correlation analysis indicated that there is a higher correlation between NPL and agriculture, Fishing, Timber, and a moderate average correlation between NPL and Hunting. Similarly, a moderate high correlation amongst individual agricultural sectors i.e. Hunting, Fishing, Agriculture, Timber and as well as higher correlation between ROA and ROE that are under consideration. This shows that there is somehow acceptable interconnectedness among the group. The results of the spillover index effects through Dielbold and Yilmaz procedure revealed a total spillover effect 57.3%. Whereas, another unexplained effect in this study is 43.7% which might be as a result random noise in the dataset due to impact of Covid-19 pandemic. This research is significant as it is first of its kind on a proof of spillover from the empirical viewpoints as it related to Turkey on level of spillover and its impacts on the NPLs of the banking sector measuring the agricultural sector’s contribution.